Taiji Ruler: Legacy of the Sleeping Immortal - Kenneth S. Cohen (Universidad de León, 2012)
This article describes the history, development, and principles of the two major Taiji Ruler lineages: one associated with the Song Dynasty (960-1279 CE) imperial family, and the other lesser known, Daoist lineage, transmitted by Hu Yaozhen and his successors, including the well known Chen Style Taijiquan teacher, Feng Zhiqiang. The Taiji Ruler is a traditional system of health-enhancing qigong that is attributed to the Song Dynasty Daoist recluse Chen Xiyi and was first taught publicly in the 1950s. The exercises may be practiced while holding a foot-long wooden object, the Ruler, or with a variety of training devices, such as a wooden or stone ball. Mr. Cohen began studying Taji Ruler with various teachers more than 30 years ago, but also bases his research on works in Chinese and English. Both the teachers and literature agree that the ultimate goal of the Ruler is to blend with the original qi of the universe and, in the process, to achieve vitality and longevity.